Gender Differences in Entrepreneurship: Evidence From Gem Data - Tsyganova, Tatiana; Shirokova, Galina (Organizations and Markets in Emerging Economies, 2010)
Being a significant component of the contemporary business world, female entrepreneurial activity is considered a key element of economic growth worldwide, and especially in emerging markets. The present study explores gender differences in efficiency-driven countries based on the GEM data through correlation and regression analyses. An important finding of the paper is that training on starting a new business as a common factor, has a greater influence on female entrepreneurial activity. Therefore, training should be considered an essential issue when designing government policies and stimulating entrepreneurial activity in general, of both female and male entrepreneurs.